Characteristics of the innovative potential of a modern university - Andreyev, Siargei E. (Journal of the Belarusian State University. Sociology, 2023)
The role of innovations in the life of modern society is described. It is noted that the problems of managing the innovative development of Belarusian universities are being updated today. Effective solutions in this area can be obtained through the use of an open platform, which includes a system of direct links between different social institutions. One of the tools for organising the interaction of education, science, industry and business is the open innovation model. With this model, the university can not only use its own developments, but also actively involve external structures with the necessary competencies. It is argued that the success of innovative projects implemented at the institution depends on the innovative climate at the university. The results of this work can be used in the further development of the problems of higher education management in the context of digitalisation.
Keywords: innovation potential; higher education; university; innovation; digitalisation of higher education; entrepreneurship